Tinjauan Keselamatan Kerja dengan Metode Hazard and Operability Study (Hazop) - Aditiya Rizka Ramadhan; Ade Momon (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the application of K3 using the Hazard and Operability Study (HAZOP) method in increasing work productivity at UMKM XYZ. The research was conducted using the Hazard and Operability Study (HAZOP) method on several work accidents that occurred at UMKM XYZ for a certain period of time and analyzed based on data on the number of work accidents. Primary data collection was carried out by the observation method and secondary data collection by the literature method. In this study, measurements were made by taking into account likelihood and consequence, and then using a risk matrix. That is assessing the existing risk (risk assessment) by defining the criteria for likelihood and consequences (severity). The likelihood criterion used is the frequency which is calculated quantitatively according to company data or records over a certain period of time. Consequences (severity) criteria used are the consequences that workers will receive which are defined qualitatively and take into account the lost working days. So from the results of the study informed that work accidents affect work productivity.